If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(n + -3) = -21 + 3n Reorder the terms: 7(-3 + n) = -21 + 3n (-3 * 7 + n * 7) = -21 + 3n (-21 + 7n) = -21 + 3n Add '21' to each side of the equation. -21 + 21 + 7n = -21 + 21 + 3n Combine like terms: -21 + 21 = 0 0 + 7n = -21 + 21 + 3n 7n = -21 + 21 + 3n Combine like terms: -21 + 21 = 0 7n = 0 + 3n 7n = 3n Solving 7n = 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 7n + -3n = 3n + -3n Combine like terms: 7n + -3n = 4n 4n = 3n + -3n Combine like terms: 3n + -3n = 0 4n = 0 Divide each side by '4'. n = 0 Simplifying n = 0
| 9x^2-576=0 | | 2x+4x=-48 | | 3c^2+c-10=c^2-5 | | -2x+34=-6(8-7x)-3x | | -2x=24 | | 25y^2=45 | | 5x=-7 | | -5(-4+5v)=-6v-37 | | 15-x=9 | | 4n-7=-(n-8) | | 9x^2-729=0 | | 8-8x=90x-22 | | 9-3x=-2x+8 | | -8x^2+128=0 | | 8m+6=3(m+2) | | 7x+14=2x+149 | | 5+6x=-6x+113 | | 0=-10v^2+13v+3 | | 3x-7=-1+6x | | 2(8+4k)=3k-4 | | -2x+1=-5x+31 | | 4(8-6x)=5x-26 | | 5x^2+75x+270=0 | | x+8=-16+4x | | 32+6x=8(x+3) | | 2(5x-25)=10(x-5) | | 6+3x=-3x-6 | | -7x^2-64+112=0 | | -9+5x=3x+9 | | 2(7v+7)=28+7v | | 7-7x=2x+7 | | 11x^2-37x=0 |